Study of diversity and population status of araneid fauna of Talash Valley, Dir (L) Pakistan - Ud Din Yousufzai , Sultan; Rahman , Nosheen; Tabassum , Wafa; Inam , Sumaira; Usman Ali Hashmi , Muhammad; Safi , Amtyaz (International Journal of Biological Research, 2024)
Spiders are invertebrates belonging to the phylum Arthropoda, class Arachnida, and order Araneae. Arachnids are one among the largest and most diverse groups, with 129 families, 4234 genera and 49,773 species. Spiders are carnivorous and polyphagous in nature. They are most effective against pests. This study was carried out to examine the arachnoid fauna status and diversity in Talash Valley, Lower Dir district of KPK. Spiders were collected from different parts of the study area. The surveyed period wss from April to July 2022 and was done by hand picking and beet crushing method. Most spiders are collected by hand. The collected samples were then stored in 70% ethanol solution. Spiders are identified with the help of available information. A total of 10 families were identified. These are Salticidae, Lycosidae, Sparassidae, Pholcidae, Hersilidae, Gnaphosidae, Oxyopidae, Araneidae, Scytodidae and Therididae. The dominant families in this study are salicidae with three species, lycosidae and sparassidae with two species each, and seven other families with one species each.